OPTIMIZATION OF THE DISTRIBUTION OF FISH USING THE METHOD OF THE CHEAPEST INSERTION HEURISTIC AT THE PLACE OF FISH AUCTION IN PANTAI LABU - Lina Safrina; Falahuddin Kusuma (Journal of Mathematics and Scientific Computing With Applications, 2021)
Every day the distribution of fish should be done given the high demand distribution. Order optimal travel route to the area of the destination to be estimated by courier in a one-time distribution. Estimated travel route that randomly causes less maximum time of travel and the high cost of so needed a solution where the route of the trip can be optimized to be more cost-saving and meminimalir long time travel at the time of the distribution. This research create a system to optimize the route of travel distribution. The method used in this research is using the method of the Cheapest Insertion Heuristic (CIH), which is a method for finding the distance smallest insertion of a new value by looping to form the optimal travel route. The system displays the results of the travel route distribution using a graph model. The results of the testing carried out from testing of the process of determining the route distribution in a Fish Auction Place (TPI) is a system of distribution of fish using the Method of the Cheapest Insertion Heuristic that generates a travel route that is optimal in terms of travel time and total distance distribution.